MODIFIED METHOD OF INGUINAL HERNIOPLASTY - S. A. Aliev; E. S. Aliev (Вестник хирургии имени И.И. Грекова)
The work is devoted to the hernioplasty method, which provides the strengthening of back wall of the inguinal canal by autogenous tissues, which were the walls of the hernial sac. After dissection of hernial sac, two muscle flaps were formed and fixed to transverse fascia on the whole perimeter of the inguinal canal. The control group consists of 64 patients and main group — 66 (90.4%). The Liechtenstein operation was performed in control group. In contrast, the method, suggested by the authors, was used in the main group. The patients with hernioplasty were carefully and sufficiently examined in order to make an objective comparative analysis of the results. The results of the review allow the authors to confirm, that the suggested hernioplasty method provides stable local homeostasis of tissues and high quality of life.